Determination of Losartan and Losartan Carboxylic acid in Human Plasma by New HPLC Method with Fluorescence Detection for Pharmacokinetics Studies - Ahmed Abbas Hussein (College of Pharmacy / Mustansiriyah University, 2014)
Losartan is highly effective blood pressure lowering agent who directly works by selectively blocking angiotensin-I (AT-I) receptor. It is primarily metabolized in active form, losartan carboxylic acid. A sensitive and selective HPLC method was developed for determination of losartan and losartan carboxylic acid in human plasma was developed and validated. The drug and its metabolite were extracted from plasma by liquid-liquid extraction with t-Methyl butyl ether. Valsartan was used as internal standard. A Waters Associates Inc. (Milford, MA, USA) Liquid chromatography was used to complete this study. The analytical apparatus consisted of a 600 quaternary pump and a fluorescence detector. Samples were applied to a repacked 5 μm, 250 x 4.6 mm CN column using auto sampler. Flow rate of 1.25 ml/min was found to give adequate resolution. Separations were performed at 35ºC and monitored at an excitation wavelength of 250nm and an emission wavelength of 370nm. Mobile phase was prepared by mixing 0.015M phosphoric acid (pH 2.3): acetonitrile in a ratio of 72:28. Linearity was established for the range of concentrations 2-300 ng/ml and 3-375 ng/ml for losartan and metabolite respectively. The lower limit of quantitation (LLOQ) was identifiable and reproducible at 2 ng/ml with a precision of 3.28% and at 3 ng/ml with a precision of 2.59% for the drug and metabolite respectively. The inter batch, between days precision at 3 ng/ml level was found to be 8.07% for losartan. The inter batch, between days precision at 5 ng/ml level was found to be 4% for the metabolite. The precision and accuracy were established at low, medium and high concentration levels. The results were within the accepted limits. The analysis method was found to be sensitive, accurate, and precise for the quantification of losartan and its metabolite in human plasma. It was applied successfully, for pharmacokinetics studies.